El programa literario argentino en marcha: las novelas del Ciclo de la Tiranía (1851-1863). - Molina, Hebe Beatriz (Estudios de Teoría Literaria, 2026)
The Argentine Generation of 1837 proposed a foundational program in pursuit of a national, socialist and progressive literature, which constituted an original literary theory. Although they are based on the multifaceted ideology of European Romanticism, they achieve a peculiar synthesis, which responds to the interpretation they make of the historical-political moment that Argentina is experiencing. This theoretical proposal is then concretized in texts that respond to various generic modalities. The most innovative is the prospectively historical novel, created to remember the terror of the government of the "tyrant Rosas" by José Mármol with Amalia (1851-1852) and Juana Paula Manso with Misterios del Plata (1852). Fifteen novels of different lengths repeat this model until 1863; a set that we call the Cycle of Tyranny. The purpose of this article is to demonstrate, from the perspective of Historical Poetics and the Theory of Polysystems, that the distinctive rule or repertorema of this form is not so much the denunciation against Rosas, as the prevention against new tyrants and that, consequently, this generic modality concretizes the foundational literary program; in particular, in terms of shaping a more democratic future for the New Nation. We will take Manso's novel as an example.